Relação entre poluição do ar e internações de idosos por doenças cardiovasculares em Cubatão e São Paulo entre 2000 e 2012 - Oliveira, Ariádna Ferraz de (2014)
Introduction: environmental pollution and its impact on health is now considered a public health problem. Despite the incessant search for an environment with cleaner air, pollution levels are still unhealthy and are related to the human morbidity and mortality. Objective: to evaluate the relationship between exposure to air pollution and hospitalizations in the Sistema Único de Saúde (SUS) of the elderly for cardiovascular diseases (CVD) totals in residents of the cities of Cubatão and São Paulo between 2000 to 2012, stratified by sex. Methods: This is an ecological study of temporal series. Schedules data were obtained on the levels of PM10, CO, SO2, NO2 and O3, minimum temperature and humidity average along the Environmental sanitation technology company in the State of São Paulo-CETESB. The hospitalizations in the Sistema Único de Saúde (SUS) were obtained from the database of the SUS (DATASUS). Descriptive analysis was performed and the Pearson correlation analysis. The association of air pollutants and cardiovascular admissions was assessed using a polynomial distributed lag model through 7 days after exposure. The log of cardiovascular admissions was regressed assuming a Poisson distribution in a generalized linear model adjusted for long time trend, weekdays, temperature and humidity. The percentage increases in the cardiovascular admissions were calculated based on the interquartile range of the air pollutants. It was adopted a significance level of 5%. Results: In the study period were admitted in the SUS 1,287,204 (19.7%) seniors, these 358970 (27.9%) with cardiovascular diseases in São Paulo. In Cubatão 13,998 were admitted (14.4%) seniors, these 3,729 (26.6%) for cardiovascular diseases. In São Paulo associations were observed between the pollutants PM10, SO2, NO2 and CO and the CVD. For each increase of an interquartile range in level of PM10 (24.42 ¿g/m3) increase hospitalizations in 2.04% (CI95%: 1.42%-2.66%), for SO2 (7.48 ¿g/m3) the increase is 2.22% (CI95%: 1.60%-2.84%), for NO2 (51.89 ¿g/m3) is 2.55% (CI95%: 1.96% ¿ 3.14%) and CO (1.33 ppm) is 1.06% (CI95%: 0.50%-1.62%). In Cubatão only the PM10 presented effect on hospitalization for CVD, where for each increase of an interquartile range in level of PM10 (39.40 ¿g/m3) increase the hospitalizations in 6.01% (CI95%: 1.61%-10.41%). Conclusion: The air pollutants continue to be one of the factors that contribute to the increase in the number of hospitalizations for cardiovascular diseases.